Hypothermic machine perfusion in kidney transplantation. Issue 3 (June 2016) - De Deken, Julie; Kocabayoglu, Peri; Moers, Cyril
Abstract : Purpose of review: This article summarizes novel developments in hypothermic machine perfusion (HMP) as an organ preservation modality for kidneys recovered from deceased donors. Recent findings: HMP has undergone a renaissance in recent years. This renewed interest has arisen parallel to a shift in paradigms; not only optimal preservation of an often marginal quality graft is required, but also improved graft function and tools to predict the latter are expected from HMP. The focus of attention in this field is currently drawn to the protection of endothelial integrity by means of additives to the perfusion solution, improvement of the HMP solution, choice of temperature, duration of perfusion, and machine settings. HMP may offer the opportunity to assess aspects of graft viability before transplantation, which can potentially aid preselection of grafts based on characteristics such as perfusate biomarkers, as well as measurement of machine perfusion dynamics parameters. Summary: HMP has proven to be beneficial as a kidney preservation method for all types of renal grafts, most notably those retrieved from extended criteria donors. Large numbers of variables during HMP, such as duration, machine settings and additives to the perfusion solution are currently being investigated to improve renal function and graft survival. In addition, the search for biomarkers has become a focus of attention to predict graft function posttransplant.